A clinico-pathological study of schistosomiasis in South Central Africa. - Gelfand, Michael (Department of Integrative Biomedical Sciences (IBMS), 2020)
A study of bilharziasis as a whole, based largely on pathological and clinical experience, has not been attempted in Africa outside of Egypt. The most impressive work in Egypt in this connection is that Fairley on the experimental infection of monkeys, which he published in 1920. Elsewhere in Africa, a number of smaller publications dealing with a particular or restricted clinical branch of schistosomiasis has been contributed by various authors, notably from South Africa. Th most important of these is Cawston. Valuable contributions from the Congo were made by such workers as Fisher and Chesterman. From West Africa particular mention must be made of Blacklock, and from Nyasaland of Dye and Gopsill. Interesting clincial papers have also been published on bilharziasis from East Africa.